TELAAH PENERAPAN SISTEM INFORMASI MANAJEMEN PADA BADAN AMIL ZAKAT INFAQ DAN SHADAQOH - Hisamuddin, Nur (ZISWAF, 2016)
Indonesia has great potential zakat due predominantly Muslim. Based on the study Baznas potential zakat fund is expected to reach 217 trillion. The amount of zakat fund management requires good management, transparency and accountability. The number of transactions and the amount of assets under management makes information management system ZIS an important part in the management process. However, the constraints of the application of management information system ZIS common in zakat management institutions.Sharia enterprise theory states that people should take responsibility for his actions not only in the world but also in the hereafter. The information system is a system to help accountability. Accounting information system is an information system that contains data or components of both physical and non-physical that interact are then processed to produce useful information for the parties concerned.